Learning Outcomes in Geometry at Secondary Stage - Chaurasia , P. K. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Geometry is recognized as not only one of the most important components of the school mathematics curriculum but also, alongside algebra, as one of the most important elements of mathematics itself. The reasons for including geometry in the school mathematics curriculum are providing opportunities for learners not only to develop spatial awareness, geometrical intuition and the ability to visualize, but also to develop knowledge and understanding of, and the ability to use, geometrical properties and theorem. In general, the twin concerns of the mathematics curriculum are: What can mathematics education do, to engage the minds of every student and strengthen the student‘s resources? As mathematics is a compulsory subject at the secondary stage, access to quality mathematics education is the right of every child. So, while talking about quality mathematics education, in general, in what sense ―the learning outcome‖ can be understood? In fact, ‗curricular expectations‘ define what a child should know, be able to do and dispositions that should be acquired over a period of time. Learning outcomes are derived from curricular expectations and syllabus is provided to help all the stakeholders in understanding the goals to be achieved. The learning outcomes are generally treated as assessment standards or benchmarks for assessment. Children are often assessed with paper pencil tests, which include certain types of questions without proper analysis whether these questions have potential to assess child‘s level of understanding in a particular class. There is a need for a teacher to understand how children progress in learning continuum of mathematics, how children‘s learning matches with the expectations of curriculum and what pedagogies she/he has to adopt for maximizing child‘s learning. This article deals with, expectations of the mathematics curriculum at secondary stage, especially for Geometry portion. Here, we try to explore the learning outcomes in Geometry for Secondary Stage Mathematics along with some suggested pedagogical processes, which may be undertaken to achieve the outcomes. These pedagogical processes are not exhaustive. They are suggestive in nature, and may vary according to the learner‘s context.